Philadelphia Paper - Burnishing and Ductilizing Steel - Jacob Reese (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1881)
I have discovered a new method by which steel and other metals may be burnished by the automatic action of the burnishing machine, and by which the cost is greatly diminished, and more perfect work produced. And in addition to the polishing and burnishing action of